A hermeneutic analysis of delusion content from the casebooks of the Grahamstown Lunatic Asylum, 1890–1907 - Rory du Plessis (South African Journal of Psychiatry, 2019)
Background and objectives: This study sought to investigate the content of the delusions recorded in the casebooks of the Grahamstown Lunatic Asylum as a means to explore how the colonial context shaped or influenced psychopathology. To this end, the study aimed to (1) identify the sociopolitical events of the time period that were reflected in the delusion content presented by the patients and (2) pinpoint discernible patterns in the delusion content based on the race and gender of the patient. The study was delimited to the period of Dr T.D. Greenlees’ tenure as medical superintendent, 1890–1907.